The divergent effects of fear and disgust on unconscious inhibitory control. Issue 4 (18th May 2016) - Xu, Mengsi; Ding, Cody; Li, Zhiai; Zhang, Junhua; Zeng, Qinghong; Diao, Liuting; Fan, Lingxia; Yang, Dong
Abstract : Previous studies have shown that negative emotional distracters impair conscious inhibitory control. Recent research has shown that inhibitory control can be triggered unconsciously; therefore, in Experiment 1, we aimed to investigate whether negative emotional distracters affect unconscious inhibitory control. Furthermore, in Experiment 2, we examined whether fearful and disgusting distracters have differential effects on unconscious inhibitory control. Participants were instructed to perform a masked Go/No-Go task superimposed on a negative or neutral image cue (Experiment 1) or on a fearful, disgusting or neutral image cue (Experiment 2). Results showed that negative emotional distracters impaired unconscious inhibitory control; furthermore, disgusting distracters impeded unconscious inhibitory control when compared to fearful ones. This study is the first to provide evidence that fear and disgust may affect unconscious inhibitory control differently. These results expand the understanding of the relationship between emotions and inhibitory control.